Development of an optimized greenhouse automation system - Cheng, Sven Erikson L. (Animo Repository, 2019)
© 2019, World Academy of Research in Science and Engineering. All rights reserved. ZIGBEE is widely used in applications that involved in monitoring and communicating functions. ZIGBEE technology is used in monitoring and controlling the growth of a potato plant inside a greenhouse system. It communicates wirelessly to sensor circuits to maintain the overall aspect needed for a suitable environment in growing potatoes. Light, Water, and Temperature are some of the factors being controlled. The purpose of this thesis is to look into the possibility of using ZIGBEE in Greenhouse application.